2013
DOI: 10.1124/mol.113.087692
|View full text |Cite
|
Sign up to set email alerts
|

Functional Validation of Virtual Screening for Novel Agents with General Anesthetic Action at Ligand-Gated Ion Channels

Abstract: GABA A receptors play a crucial role in the actions of general anesthetics. The recently published crystal structure of the general anesthetic propofol bound to Gloeobacter violaceus ligand-gated ion channel (GLIC), a bacterial homolog of GABA A receptors, provided an opportunity to explore structure-based ligand discovery for pentameric ligand-gated ion channels (pLGICs). We used molecular docking of 153,000 commercially available compounds to identify molecules that interact with the propofol binding site in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…For example, the limited solubility of an average ‘hit’ molecule in some cases prevented effective evaluation with ITC, and ITC is low to moderate through-put. Another approach could involve reversing the common paradigm of starting with a virtual screen (“docking”) followed by confirmatory tests, 25 to start with the physical screen and confirm hits with docking to the target in question (in this case apoferritin) It is important to note that the success of any virtual “docking” approach depends on the quality of target three-dimensional structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the limited solubility of an average ‘hit’ molecule in some cases prevented effective evaluation with ITC, and ITC is low to moderate through-put. Another approach could involve reversing the common paradigm of starting with a virtual screen (“docking”) followed by confirmatory tests, 25 to start with the physical screen and confirm hits with docking to the target in question (in this case apoferritin) It is important to note that the success of any virtual “docking” approach depends on the quality of target three-dimensional structures.…”
Section: Discussionmentioning
confidence: 99%
“…The logED50 of propofol (mmol/kg) in mice has previously been reported as −1.03. 25 Loss-of-righting reflex after iv administration of ML306 (B) and 14 (C.) Both ML306 and 14 produced increased duration of loss of righting reflex in a dose-dependent fashion ( p < 0.05 by one-way ANOVA with Tukey’s multiple comparisons test), though duration was considerably longer with administration of 14.…”
Section: Figurementioning
confidence: 99%
“…Computational [208, 210] and thiolabeling studies [215] indicated this intrasubunit site plays only a limited role in canonical GLIC modulation. Nonetheless, computational screening of novel ligands based on this site yielded compounds that modulated GABA A receptors [216]; furthermore, photolabeling [217] and NMR analyses [218] implicated an equivalent site in nicotinic receptors, indicating that even relatively silent sites in one drug-receptor system could be relevant in another.…”
Section: Key Questions Subject To Interdisciplinary Study In Ion Tmentioning
confidence: 99%
“…Several studies have combined molecular dynamics and docking calculations to predict multiple VA binding sites 37,42,43 or quantify VA affinities to two different cavities 31 . As new anesthetic binding pockets are identified, it will even be possible to perform virtual screenings for new anesthetics, as has been done for the propofol binding site in GLIC 44 . The increasing number of crystal structures and the advances in computational techniques will ultimately be used to resolve the enigma surrounding the mechanism of action of VAs.…”
Section: X-ray Structures Of Prokaryotic and Invertebrate Plgicsmentioning
confidence: 99%